Cellular signaling on host-malaria parasite interactions - Regina da Silva Garcia, Celia (Henry Stewart Talks, 2012)
Plasmodium signaling, Control of the cell cycle mechanisms, Clinical and diagnostic applications in malarial research, Live cell microscope work, Molecular techniques